Freeze dried chitosan acetate dressings with glycosaminoglycans and traxenamic acid. (15th March 2018) - Saporito, Francesca; Sandri, Giuseppina; Rossi, Silvia; Bonferoni, Maria Cristina; Riva, Federica; Malavasi, Lorenzo; Caramella, Carla; Ferrari, Franca
Highlights: Mechanical and bioadhesive properties of chitosan/glycosaminoglycan dressings are suitable to treat bleeding wounds. Chitosan and glycosaminoglycan interaction was studied by FTIR and dressing morphology was characterized by SEM. Chitosan and tranexamic acid have a synergic effect in clot formation. Abstract: Bleeding control plays an important role to increase survival in the early phase after a traumatic event. The aim of present work was the development of hemostatic sponge-like dressings based on chitosan, in association with glycosaminoglycans (GAG) (chondroitin sulfate or hyaluronic acid) and the improvement of their hemostatic performance by loading tranexamic acid (TA). The dressings were prepared by lyophilizazion and were characterized for mechanical, hydration, bioadhesion properties and morphology. Moreover, FTIR analysis was performed to understand the interactions between the different polyelectrolytes present in the dressings. Clotting was investigated in vitro by using rat whole blood. Moreover, in vitro biocompatibility and proliferation were evaluated towards fibroblasts. Ex vivo proliferation properties were assessed by using human skin. All the dressings were characterised by mechanical, hydration and bioadhesion properties suitable to be applied on bleeding wounds and to absorb bleeding or wound exudate, avoiding tissue dehydration. TA release was fast; TA and chitosan showed a synergic effect to speed up clotting. The dressings were biocompatible and able to sustain cell proliferation in vitro and ex vivo in human skin. In conclusion, sponge-like dressings based on chitosan and GAG and loaded with TA are an effective tool to enhance hemostasis and healing in bleeding wounds.